Análise da influência da variação de temperatura no desempenho de pavimentos asfálticos à fadiga a partir da modelagem viscoelástica - Chaves, Bruno de Souza (2021)
Brazilian highways have a great deficiency in regards to its use conditions and one of the main pathologies observed is fatigue cracking. One of the most influential factors in pavement fatigue performance is temperature. Presently, this factor is not taken into account in the current design method (DNER, 1981). In MeDiNa, which is the new proposal for pavement design method, it is considered a fatigue model based on a constant temperature of 25 °C. Given the great thermic variations to which an asphalt pavement can be subjected, mainly in subtropical climate regions, that is the case of Rio Grande do Sul, it is significant to investigate how much does temperature and its variations influence pavement life cycle. In light of this, the current research adopts an approach that considers the influence of temperature, through viscoelastic continuum damage (VECD) analysis, with the aid of software FlexPAVE™. Therefore, with complex module and uniaxial tension-compression fatigue tests as inputs, with temperature data that simulate climatic conditions of the central region of Rio Grande do Sul, it was possible to obtain the fatigue damage of the pavement along the time. Besides this, through the application of transfer functions, the percentage of cracked area to each simulation was predicted, just as the pavement life cycle with an mechanistic-empirical, implemental cost approach. It was verified in the results that temperature has great influence not only in fatigue damage, but also in cracked area prediction and pavement life cycle. Comparing the results with those obtained from MeDiNa, a comparative economic analysis was realized and it showed that VECD model, coupled with realistic temperature estimate, is an important tool in pavement fatigue analysis and cracked area prediction.